2020
DOI: 10.1038/s41598-020-64424-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterisation of enteroaggregative Escherichia coli subtypes associated with human disease

Abstract: Enteroaggregative E. coli (EAEC) are a major cause of diarrhoea worldwide. Due to their heterogeneity and carriage in healthy individuals, identification of diagnostic virulence markers for pathogenic strains has been difficult. In this study, we have determined phenotypic and genotypic differences between EAEC strains of sequence types (STs) epidemiologically associated with asymptomatic carriage (ST31) and diarrhoeal disease (ST40). ST40 strains demonstrated significantly enhanced intestinal adherence, biofi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 58 publications
1
30
0
1
Order By: Relevance
“…Regarding the ST40 clone, a relation between diarrheal disease and the presence of this lineage (containing specific virulence genes) was recently found among clinical isolates from patients in the United Kingdom [55]. Furthermore, the ST429 lineage was found in our study in CMY-2-and CTX-M-15-producing isolates of healthy cats.…”
Section: Discussionsupporting
confidence: 70%
“…Regarding the ST40 clone, a relation between diarrheal disease and the presence of this lineage (containing specific virulence genes) was recently found among clinical isolates from patients in the United Kingdom [55]. Furthermore, the ST429 lineage was found in our study in CMY-2-and CTX-M-15-producing isolates of healthy cats.…”
Section: Discussionsupporting
confidence: 70%
“…The results point to several extremely interesting facts. This bacterium undoubtedly has considerable influence on human and animal lives [ 47 , 48 ], for the simple reason that it lives inside the gut and can very easily spread from fecal matter to the mouth [ 49 , 50 ]. Being the commensal bacteria of human and animal gut, it happens to be in close contact with numerous other bacteria [ 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown evidence that EAEC and EPEC pathotypes are isolated from both symptomatic and asymptomatic individuals [15, 16]. The pathogenic potential of DEC is influenced by a number of different factors, including host susceptibility, the ingested bacterial load and the presence of virulence genes and the different subtypes and combinations of these virulence genes [17–19]. Where EPEC and/or EAEC are detected in patients reporting to primary health care with symptoms of gastrointestinal disease, where no other gastrointestinal pathogens are detected, these DEC pathotypes may be considered as the aetiological agent, particularly if the patient reports recent travel outside the UK, or in the case infection with EPEC the patient is aged 2 years or under [17, 20].…”
Section: Discussionmentioning
confidence: 99%